Factors Influencing the Level of Knowledge in Identifying Warning Signs of Cancer. (March 2020) - Ismail, I; Abd Razak, N F; Jamalul, J; Abdullah, N A I; Ramle, N S H
Abstract: Cancer can be defined as an uncontrolled and unregulated growth of cell in human body and it can be diagnosed in all level of age, races and also both genders. High level of awareness and adequate knowledge of warning signs of cancer might have great impact in surviving the disease. A cross-sectional study was done to determine the level of knowledge in identifying warning signs of cancer among students in Universiti Teknologi MARA (UiTM) Kota Bharu Campus and to examine the factors that contribute significantly to the level of knowledge. There are 9 independent variables involved in this study; gender, CGPA, father's education level, mother's education level, family's monthly income, health insurance status, family history of having cancer, BM, and age. The dependent variable in this study is level of knowledge in identifying warning signs of cancer where it is categorized into 0 and 1; 0 denoting low knowledge and 1 denoting high knowledge. The finding shows that most of the respondents have low level of knowledge (84.9%). Multiple logistic regression analysis was performed to identify the determinants of level of knowledge in identifying warning signs of cancer. Overall, there were two significant variables (family monthly income and family history of having cancer) found in logistic regression analysis. There are several recommendations highlighted in this study such as the strategies to communicate the warning signs of cancer to the public.